Stability of Rotation Pairs of Cycles for the Interval Maps - Taixiang Sun; Hongjian Xi; Hailan Liang; Qiuli He; Xiaofeng Peng (Abstract and Applied Analysis)
Let C0(I) be the set of all continuous self-maps of the closed interval I, and P(u,v)={f∈C0(I):f has a cycle with rotation pair (u,v)} for any positive integer v>u. In this paper, we prove that if (2mns,2mnt)⊣(γ,λ), then P(2mns,2mnt)⊂  int  P(γ,λ), where m≥0 is integer, n≥1 odd, 1≤s<t with s,t coprime, and 1≤γ<λ.